Turkish foreign policy-making vis-à-vis the Ukraine crisis: From Sevres syndrome and russophobia perspective - Akıncı, Basri Alp (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
Ukrayna krizi özelinde Türk dış politikası yapımı: Bir Sevr sendromu ve rusofobi bakışıyla